Persoalan Eksplorasi Sumber Daya Timah di Pulau Bangka dalam Perspektif Teori Sosial Kritis Mazhab Frankfurt - Herza, Herza; Nur Faizza Tunnisa; Ramadhani, Tiara; Darmawan, Budi; Nova, Chelsea (Equilibrium: Jurnal Pendidikan, 2025)
This paper focuses on analyzing the massive tin mining issue on Bangka Island through the lens of the First Generation Frankfurt School’s critical social theory, particularly the ideas of Horkheimer and Adorno concerning the consequences of instrumental or technological rationality. The study employs a qualitative approach using a literature review method, elaborated with field observations for data collection. The analysis reveals the continuing relevance of the First Generation Frankfurt School’s thought in understanding modern human problems rooted in instrumental rationality, as reflected in the large-scale exploitation of tin resources. A critical examination indicates that the root cause of this phenomenon lies in the epistemic foundation of the state’s and local elites’ approach to resource management—through PT Timah (formerly PT Kobatin)—which is characterized by what Horkheimer terms instrumental rationality and what Adorno refers to as technological rationality. This mode of reasoning prioritizes effectiveness, efficiency, and profit orientation, often at the expense of environmental integrity and human well-being. Empirical evidence of environmental degradation is evident in unreclaimed mining pits (kolong), damaged mangrove ecosystems, marine pollution leading to the loss of fishermen’s livelihoods, and a widening socio-economic gap between elites and field laborers.